\(\left|2x+1\right|=\left|12x-5\right|\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,=\dfrac{2y^4}{3x\left(2x-3y\right)}\\ b,=-\dfrac{2y\left(3x-1\right)^2}{3x^2}\\ c,=\dfrac{5\left(4x^2-9\right)}{\left(2x+3\right)^2}=\dfrac{5\left(2x-3\right)\left(2x+3\right)}{\left(2x+3\right)^2}=\dfrac{5\left(2x-3\right)}{2x+3}\\ d,=\dfrac{5x\left(x-2y\right)}{-2\left(x-2y\right)^3}=-\dfrac{5x}{2\left(x-2y\right)^2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
B: rút gọn
a) Ta có: \(\left(x-2\right)\left(x^2+2x+4\right)-6x^2+12x\)
\(=x^3-6x^2+12x-8\)
\(=\left(x-2\right)^3\)
b) Ta có: \(\left(2x+5\right)\left(5-2x\right)+\left(x-5\right)\left(4x+5\right)\)
\(=25-4x^2+4x^2+5x-20x-25\)
=-15x
![](https://rs.olm.vn/images/avt/0.png?1311)
\(8x^3-12x^2y+6xy^2-y^3=8\)
\(\Leftrightarrow\left(2x-y\right)^3=8\)
\(\Leftrightarrow2x-y=2\)
\(\Rightarrow y=2x-2\)
Thế xuống pt dưới:
\(\left(x^2-2x-2\right)\left(-3x^2+6x-9\right)=14\)
Đặt \(x^2-2x=t\)
\(\Rightarrow\left(t-2\right)\left(-3t-9\right)=14\)
\(\Leftrightarrow...\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Giải:
a) \(\left(3x-1\right)^2-\left(2x+3\right)^2=0\)
\(\Leftrightarrow\left(3x-1+2x+3\right)\left(3x-1-2x-3\right)=0\)
\(\Leftrightarrow\left(5x+2\right)\left(x-4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}5x+2=0\\x-4=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{2}{5}\\x=4\end{matrix}\right.\)
Vậy ...
b) \(\left(12x-5\right)\left(4x-1\right)+\left(3x-7\right)\left(1-16x\right)=81\)
\(\Leftrightarrow48x^2-20x-12x+5+3x-7-48x^2+112x=81\)
\(\Leftrightarrow83x-2=81\)
\(\Leftrightarrow83x=83\)
\(\Leftrightarrow x=1\)
Vậy ...
\(\left|2x+1\right|=\left|12x-5\right|\)
\(\Rightarrow\left[{}\begin{matrix}2x+1=12x-5\\2x+1=-12x+5\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}6x=6\\14x=4\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=1\\x=\dfrac{4}{14}=\dfrac{2}{7}\end{matrix}\right.\)